Physical Activity and Sedentary Behavior During COVID-19: Trajectory and Moderation by Personality. Issue 6 (August 2021) - Stephan, Yannick; Terracciano, Antonio; Luchetti, Martina; Aschwanden, Damaris; Lee, Ji Hyun; Sesker, Amanda A.; Strickhouser, Jason E.; Sutin, Angelina R.
The present study examined the relation between personality and changes in physical activity and sedentary behaviors during the acute phase of the 2019 coronavirus disease (COVID-19) pandemic. Personality was assessed prior to the coronavirus crisis in the Understanding America Study (UAS, N = 6, 702) and the Psychological, Behavioral, and Social Response (PBSR) to the coronavirus pandemic ( N = 3, 992) study. Physical activity was assessed 4 times from March 2020 to May 2020 in the UAS, and sedentary behavior was assessed 3 times from January 2020 to April 2020 in the PBSR. Higher neuroticism was associated with less increase in physical activity, whereas higher conscientiousness and agreeableness were related to a steeper increase in physical activity over time in the UAS. In the PBSR, higher neuroticism and lower extraversion, agreeableness, and conscientiousness were related to higher average sedentary behavior. This study provides new evidence that personality predicts behavioral responses to the COVID-19 crisis.